The Impact of Normalization of Batang Agam Watershed in Payakumbuh City - Putri Warseno, Diyas; Wulan, Diah Retno (Marcapada: Jurnal Kebijakan Pertanahan, 2023)
Watershed normalization of Batang Agam was initiated in 2015 and continued until 2022 with a substantial budget allocation. But what has been the extent of its impact? Furthermore, it is essential to explore the alignment between the Detailed Spatial Plan (RDTR) of Payakumbuh City and the actual land acquisition process for normalization in three neighborhoods: Pakan Sinayan, Tanjung Pauh, and Tanjunggadang Sungai Pinago located in West Payakumbuh Subdistrict. This qualitative research, conducted through observation and surveys, delves into the implementation of normalization and the subsequent impacts it has caused. Normalization can be successful due to the support from various potential factors, including legal regulations, stakeholder collaboration, adequate funding, and community participation. Normalization brings about positive impacts across environmental, social, and economic aspects. However, it turns out that normalization also has negative impacts, such as natural responses to changes and physical developments, as well as various community activities that lack responsiveness to environmental sustainability.